Encountering religion in the workplace : the legal rights and responsibilities of workers and employers - Gregory, Raymond F., 1927- (Ithaca : ILR Press, 2011)
In a recent survey, 20 percent of the workers interviewed reported that they had either experienced religious prejudice while at work or knew of a coworker who had been subjected to some form of discriminatory conduct. Indeed, according to the Equal Employment Opportunity Commission, the filing of religious discrimination charges under Title VII of the Civil Rights Act of 1964 (which prohibits discrimination in employment based on race, color, national origin, sex, and religion) increased 75 percent between 1997 and 2008. The growing desire on the part of some religious groups to openly express their faith while at work has forced their employers and coworkers to reconsider the appropriateness of certain aspects of devotional conduct. Religion in the workplace does not sit well with all workers, and, from the employer's perspective, the presence of religious practice during the workday may be distracting and, at times, divisive. A thin line separates religious self-expression, by employees and employers, from unlawful proselytizing. In this work, the author presents specific cases that cast light on the legal ramifications of mixing religion and work, in the office, on the factory floor, even within religious organizations. Court cases arising under Title VII and the First Amendment must be closely studied, he argues, if we are to fully understand the difficulties that arise for employers and employees alike when they become involved in workplace disputes involving religion.
Religious Discrimination in the Workplace. Is there a place for religion in the workplace? -- What is religion as defined by law? -- Religious discrimination and the Civil Rights Act of 1964 -- Religious discrimination at various stages of the employment relationship -- Religious discrimination claims arising out of the termination of employment -- Employee proselytization -- Employer proselytization -- Employer liability for employee acts of religious harassment -- Workplace discrimination and certain religious groups -- Religion in the Public-Sector Workplace. Proselytizing in the public-sector workplace -- Exemptions to Discrimination Laws. Exemptions from the discrimination laws granted to religious organizations -- The ministerial exception -- Questionable applications of the ministerial exception -- Accommodating Worker Religious Practices. General principles of accommodation -- Accommodation in practice -- Accommodation in out-of-the-ordinary circumstances -- Retaliation and Other Issues. Religious discrimination and retaliation -- Some additional issues -- Religion and the law in the workplace of the future -- LIst of cases discussed in the book.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Religion in the workplace -- Law and legislation -- United States; Religion in the workplace -- Law and legislation; United States; LAW / Administrative Law & Regulatory Practice; Electronic books